Intermolecular Forces Driving Hexamethylenetetramine Co-Crystal Formation, a DFT and XRD Analysis - Giovanni Bella; Francesco Nicolò; Giuseppe Bruno; Antonio Santoro (Molecules, 2021)
Interest in co-crystals formation has been constantly growing since their discovery, almost a century ago. Such success is due to the ability to tune the physical-chemical properties of the components in solid state by avoiding a change in their molecular structure. The properties influenced by the co-crystals formation range from an improvement of mechanical features and chemical stability to different solubility. In the scientific research area, the pharmacological field is undoubtedly one of those in which an expansion of the co-crystal knowledge can offer wide benefits. In this work, we described the crystalline structure of hexamethylenetetramine co-crystallized with the isophthalic acid, and we compared it with another co-crystal, showing the same components but different stoichiometry. To give a wider overview on the nature of the interactions behind the observed crystal packing and to rationalize the reasons of its formation, a computational analysis on such structures was carried out.